Wind-driven coastal upwelling causes synoptic-to-intraseasonal variations in tidal temperature variability near a strong shelf front in the northern South China Sea in summer - Li, Junyi; Zhai, Fangguo; Liu, Cong; Gu, Yanzhen; Li, Peiliang; Ye, Guanqiong (Frontiers in Marine Science, 2025)
Tidal variability and coastal upwelling are some of the most important processes in global shelf seas. With observations and high-resolution numerical simulation, we investigate the synoptic-to-intraseasonal variations in tidal temperature variability to the east of the Leizhou Peninsula and Qiongzhou Strait in the northern South China Sea and clarify the underlying dynamics. The results indicate that tidal temperature variability is most significant in a narrow meridional band in shallow waters (< 40 m) to the east of the Leizhou Peninsula and Qiongzhou Strait in the summer when there are strong thermal fronts located on the sea floor slope. The summer mean diurnal standard deviation of hourly temperature can reach up to 0.93°C. Tidal temperature variability in summer exhibits no spring-neap cycles but strong synoptic-to-intraseasonal variations, with the diurnal standard deviation of hourly temperature varying significantly from 0°C to 2.36°C. Further analyses indicate that synoptic-to-intraseasonal variations in tidal temperature variability in the summer are predominantly caused by wind-driven coastal upwelling. When southerly winds are weak, coastal upwelling is weak and leads to the offshore thermal front being located far away from the Leizhou Peninsula. Waters between the offshore thermal front and the Leizhou Peninsula/Qiongzhou Strait are mixed well and experience insignificant tidal temperature variability. When southerly winds are strong, coastal upwelling is strong and results in the offshore thermal front moving westward close to the Leizhou Peninsula. This facilitates the formation of the nearshore thermal front in combination with the complex topography and tidal currents. Tidal current-induced swinging of the nearshore thermal front then generates significant tidal temperature variability. The above results highlight the importance of coastal upwelling/downwelling in modulating tidal temperature variability near ocean thermal fronts in the shelf seas.